The Origin and Diagnosis of Iron Deficiency Anemia in a Modern Interpretation - Narzullayevna, Uzoqova Oyjamol; Rayxona, Mansurova; Mehribon, Usmanova (American Journal of Bioscience and Clinical Integrity, 2025)
Anemia is a group of diseases characterized by a decrease in the number of circulating red blood cells and/or hemoglobin per unit volume of blood for a given age and gender. Most often (80-95% of all anemias) in the real clinical practice of a therapist, chronic iron deficiency anemia (IDA) is encountered. Often, when discussing various aspects of the diagnosis and treatment of IDA, one can come across the position that everything about IDA has long been known and well known. However, in real clinical practice, for various reasons, pitfalls, reefs and shallows are forgotten, the underestimation of which can lead to certain difficulties in diagnosis and treatment. The presented review discusses the most important aspects of the diagnosis and treatment of IDA.